Analysis of shift work disorder and its influencing factors in medical staff - WANG Qin, ZHENG Yanqing, GUO Na, XING Jibin, ZHOU Shaoli (Xin yixue)
Objective To investigate the status of shift work disorder （SWD） and influencing factors in medical staff， aiming to improve individual sleep cognition and sleep behavior of medical staffs and enhance the quality of shift work sleep， thereby optimizing medical service system and benefiting the patients. Methods Five hundred medical staff were selected by random sampling method to conduct a questionnaire survey of SWD in four dimensions including the situation of waking up early and unable to fall back to sleep， the perceived comfort of waking up during night shift， the possibility of dozing off during night shift， and the situation of dozing off or falling asleep while driving after at least 2 days rest during night shift. Influencing factors of SWD were analyzed from these four dimensions by using univariate and multivariate binary Logistic regression analyses. Results Among 500 respondents， 88.2% of them experienced the situation of waking up early and unable to fall back to sleep during night shift in the past month， 88.0% for those with decreased perceived comfort of waking up during night shift in the past month， 85.2% with the possibility of dozing off during night shift in the past month and 56.0% with the situation of dozing off or falling asleep while driving after at least 2 days rest during night shift in the past month， respectively. According to the risk of SWD in all respondents， 72% of them had high-risk SWD and the remaining 28% had low-risk SWD. Multivariate binary Logistic regression analysis showed that martial status （P = 0.011 for overall test； OR = 2.322，95%CI： 1.328-4.058，P = 0.003 for married versus single）， and intake of hypnotics during non-night shift （OR = 5.678， 95%CI： 1.350-23.872， P = 0.018） were both influencing factors of waking up early and unable to fall back to sleep during night shift. Stress （OR =3.732， 95%CI： 1.072-12.996， P = 0.039） and intake of hypnotics during non-night shift （OR = 5.731， 95%CI： 1.367-24.031， P = 0.017） were influencing factors of decreased perceived comfort of waking up during night shift. Exercise （OR = 0.540， 95%CI： 0.325-0.895， P = 0.017） and stress （OR = 5.246， 95%CI： 1.616-17.025， P = 0.006） were influencing factors of dozing off during night shift. Marital status （P = 0.043 for overall test； OR = 1.509， 95%CI： 1.024-2.224，P = 0.037 for married versus single）， duration of light exposure （P = 0.003 for overall test； OR = 0.410， 95%CI： 0.208-0.825， P = 0.012 for 3~<6 h versus <1 h light exposure） and nap during night shift （OR = 0.640， 95%CI： 0.422-0.972， P = 0.036） were protective factors of dozing off while driving after at least 2 days rest. Conclusions SWD is relatively common in medical staff， especially the married and those who take hypnotics during non-night shift are at a higher risk of SWD. Relieving stress， increasing appropriate exercise， increasing nap and light exposure for 3~<6 h during night shift may help improve the quality of sleep.